2022
DOI: 10.1016/j.ajhg.2021.12.014
|View full text |Cite
|
Sign up to set email alerts
|

MRSD: A quantitative approach for assessing suitability of RNA-seq in the investigation of mis-splicing in Mendelian disease

Abstract: Variable levels of gene expression between tissues complicates the use of RNA sequencing of patient biosamples to delineate the impact of genomic variants. Here, we describe a gene-and tissue-specific metric to inform the feasibility of RNA sequencing. This overcomes limitations of using expression values alone as a metric to predict RNA-sequencing utility. We have derived a metric, minimum required sequencing depth (MRSD), that estimates the depth of sequencing required from RNA sequencing to achieve user-spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…We found that, when using fibroblasts as a source of RNA instead of whole blood RNA, RNA and data quality was higher, based on our control parameters, and more genes known to be involved in NDD could be detected. This matches a recent study showing that fibroblasts have broader gene expression than whole blood, potentially allowing identification of mis-splicing events in more individuals (64).…”
Section: Discussionsupporting
confidence: 90%
“…We found that, when using fibroblasts as a source of RNA instead of whole blood RNA, RNA and data quality was higher, based on our control parameters, and more genes known to be involved in NDD could be detected. This matches a recent study showing that fibroblasts have broader gene expression than whole blood, potentially allowing identification of mis-splicing events in more individuals (64).…”
Section: Discussionsupporting
confidence: 90%
“…Three samples had a high number of splicing outlier genes, out of which two corresponded to the ones with the highest sequencing depth. This indicates that sensitivity to splicing outliers could increase with deeper sequencing, which is in line with analyses in simulated and real datasets [ 29 , 90 ]. Power analysis for FRASER has been described in the original publication on suprapubic skin tissue from the GTEx dataset, which has a similar sequencing depth to this study’s dataset.…”
Section: Resultssupporting
confidence: 76%
“…In order to determine if the coverage extended across the entire gene, however, it is important to look at splice junction coverage. A recent paper developed a calculation for the minimum read sequencing depth (MRSD) needed to express a given gene or genes at a level sufficient for splicing [ 63 ]. Because we did not have a PBMC whole mRNA control dataset for direct comparison of MRSD with our targeted panel, we used the MRSD web tool and combined the results for whole blood and lymphoblastoid cell lines (LCLs), acknowledging that a handful of genes were likely to be specific to a given biotype.…”
Section: Resultsmentioning
confidence: 99%
“…This generally leads to arguments that the disease-relevant tissue is a necessity for RNAseq and/or that sequencing depth should be at least 50–100 M reads per sample [ 5 , 38 , 39 ]. The recent minimum read sequencing depth (MRSD) study identified whole blood (over LCL, cultured fibroblasts, and skeletal muscle) as the worst option for most gene panels [ 63 ]. However, we show that our targeted gene panel outperformed expectations and allowed us to analyze at least 20% more genes of interest than we would have been able to with whole mRNA.…”
Section: Discussionmentioning
confidence: 99%